Who wants to be a psychiatrist? Northern Ireland foundation doctors (2006–2018) are positive toward psychiatry as career choice. (August 2020) - Doris, Michael; Grimason, Amy; Hughes, Damien; O'Neill, Edel; Parks, Lorraine; Carragher, Angela
Abstract : Aims and method: Northern Ireland presents itself as an anomaly – a region in which only 31.8% of doctors enter into any training programme after completion of the Foundation Programme, but where Core Psychiatry has been consistently oversubscribed. Here, we aim to find what other regions can learn from this success. All doctors of any grade, working in psychiatry, who had been though the Foundation Programme were questioned on their motivations for becoming a psychiatry trainee. Results: Sixty-two doctors currently working in psychiatry responded, including over 60% of current trainees, and 45% stated they had not considered a career in psychiatry before their foundation attachment. Over 80% preferred foundation placements in FY2 only, rather than in either foundation year 1 or FY2. Clinical implications: This survey identifies that for the majority of people who ultimately chose to train in psychiatry, in a region that has consistently attracted candidates to core and higher level training, completion of a foundation psychiatry post was an influencing factor in this decision. A strong majority of doctors prefer the foundation psychiatry placement to be offered in FY2.